Historia de colonia La Unión, en el municipio de Nueva Guinea, RAAS, Nicaragua, 1974-2004 / José Rene Jirón Álvarez; Frank Gregorio Reyes Diaz - Jirón Álvarez, José Rene; Reyes Diaz, Frank Gregorio (2006)
Historia de colonia La Unión, en el municipio de Nueva Guinea, RAAS, Nicaragua, 1974-2004